Peripheral blood IRF1 expression as a marker for glucocorticoid sensitivity. Issue 3 (March 2015) - Chapin, William J.; Lenkala, Divya; Mai, Yifeng; Mao, Yushan; White, Steven R.; Huang, Rong S.
Abstract : Objective: Despite of the common usage of glucocorticoids (GCs), a significant portion of asthma patients exhibit GC insensitivity. This could be mediated by diverse mechanisms, including genomics. Recent work has suggested that measuring changes in gene expression may provide more predictive information about GC insensitivity than baseline gene expression alone, and that expression changes in peripheral blood may be reflective of those in the airway. Methods: We performed in silico discovery using gene expression omnibus (GEO) data that evaluated GC effect on gene expression in multiple tissue types. Subsequently, candidate genes whose expression levels are affected by GC were examined in cell lines and in primary cells derived from human airway and blood. Results: Through gene expression omnibus analysis, we identified interferon regulator factor 1 ( IRF1 ), whose expression is affected by GC treatment in airway smooth muscle cells, normal human bronchial epithelial (NHBE) cells, and lymphoblastoid cell lines (LCLs). Significant IRF1 downregulation post GC exposure was confirmed in two cultured airway epithelial cell lines and primary NHBE cells ( P <0.05). We observed large interindividual variation in GC-induced IRF1 expression changes among primary NHBE cells tested. Significant downregulation of IRF1 was also observed in six randomly selected LCLs ( P <0.05), with variable degrees of downregulation among different samples. In peripheral blood mononuclear cells obtained from healthy volunteers, variable downregulation of IRF1 by GC was also shown. NFKB1, a gene whose expression is known to be downregulated by GC and the degree of downregulation of which is reflective of GC response, was used as a control in our study. IRF1 shows more consistent downregulation across tissue types when compared with NFKB1 . Conclusion: Our results suggest that GC-induced IRF1 gene expression changes in peripheral blood could be used as a marker to reflect GC response in the airway. Abstract : Supplemental Digital Content is available in the text.